Implementation of Mellin transform using FPGA based embedded system platform - Kshitij; Rawoof, Shaik Abdul; Ray, K. C. (2012 2nd International Conference on Power, Control and Embedded Systems, 2012)
Since decades Mellin transform because of its scale invariant property has gained its attention to various real time applications such as signal and image processing including speech processing, pattern recognition and speech recognition etc. Today, all these applications demand embedded platform for real time implementation. Since the Mellin transform is one of the constituent in these applications, it needs to be implemented on embedded hardware platform to meet the real time computational requirements. To the knowledge of authors, no one have presented the implementation of Mellin transform on FPGA based embedded system platform. Recently, FPGA (Field Programmable Gate Array) based real time embedded system has taken its momentum over other commercially available hardware platforms such as microprocessors, DSP due to its features such as reconfigurability, flexibility, fast computation and less design time to market with low cost. In this context, authors have presented the implementation of Mellin transform on embedded system platform where this platform has been developed using 32-bit RISC processor (TSK-3000A) along with customized peripherals such as memory, ADC and DAC on a FPGA (Xilinx Spartan XC3S1400AN) chip. The performance of Mellin transform in this embedded platform using scaled sinusoidal signals as inputs have been analyzed which shows that the transform is scale invariant and output is very close to MATLAB simulation.